PEMBERDAYAAN MASYARAKAT MELALUI PENGEMASAN PAKET WISATA DI KAWASAN PESISIRAN PANTAI BALONG MULYO KRAGAN - Rikah Rikah; Damayanti Damayanti; Ari Susanti (RAMBIDEUN : Jurnal Pengabdian Kepada Masyarakat, 2024)
A tourism product is a system consisting of tourists, attractions, facilities and time. So, there is a need for an education-based tourism product strategy to support tourism development in the Balong Mulyo Kragan Beach area, Rembang Regency. The aim of this community service activity was to empower the community through packaging tour packages in the Balong Mulyo Beach area. Apart from that, increasing knowledge, understanding, benefits and functions of tour packages. The method for implementing this community service activities were through theoretical knowledge transfer methods, practical training and mentoring, as well as processes that emphasize abilities, knowledge, skills and attitudes. The result of this activity was a positive attitude of partners in facing the opportunities and challenges of developing a tourist village through training in making tour packages and partners can make brochure material for tour packages, as well as calculating the cost of tour packages. Training on making tour packages is carried out through training for tourism actors in the Balong Mulyo Beach area to make tour packages so that the Balasemi and Balasiem tour packages are formed including combining several village tours in Balong Mulyo, Tegal Mulyo, Plawangan. With this activities, it was found that the number of visitors increased 60.25% from 2022 to 2023 and partner income increased 35.25% from 2022 to 2023.